The efficacy of dapagliflozin combined with hypoglycemic drugs in treating type 2 diabetes: protocol for meta-analysis of randomized controlled trials - Sun, Yu-nan (BioMed Central, 2013)
BACKGROUND: Dapagliflozin is a first-in-class oral sodium glucose co-transporter 2 (SGLT2) inhibitor. It is often used in combination with conventional anti-diabetic drugs such as metformin, glimepiride, and insulin in treating type 2 diabetes (T2D). It not only reduces glucose reabsorption in the kidney but also increases renal glucose excretion. Some studies found the actions of dapagliflozin independent of insulin and free from risk of weight gain. This meta-analysis aims to evaluate whether dapagliflozin is synergistic with other anti-diabetic drugs without risk of weight gain. METHODS/DESIGN: This meta-analysis will include the randomized controlled trials (RCT) evaluating the efficacy of dapagliflozin as an add-on drug in treating T2D for >8 weeks with the outcome measures glycosylated hemoglobin (HbA1c), fasting plasma glucose (FPG) and body weight. Information of relevant RCTs will be retrieved from major databases including PubMed, Cochrane Library, Embase, ClinicalTrials.gov, and Google Scholar according to a pre-specified search strategy. Google and manual search will find other unpublished reports and supplementary data. Eligible RCTs will be selected according to pre-specified inclusion and exclusion criteria. Data will be extracted and input into a pre-formatted spreadsheet. The Cochrane risk of bias tool will be used to assess the quality of the eligible RCTs. Meta-analysis based on the random-effects model will be conducted to compare the changes of HbA1c (%), FPG (mmol/L), and body weight (kg) between dapagliflozin arm and placebo arm. Publication bias will be evaluated with a funnel plot and the Egger’s test. Heterogeneity will be assessed with the I(2) statistics. Sensitivity analysis will be conducted on follow-up periods. The evidential quality of the findings will be assessed with the GRADE profiler. DISCUSSION: The findings of this meta-analysis will be important to clinicians, patients, and health policy-makers regarding the use of dapagliflozin in T2D treatment. STUDY REGISTRATION: PROSPERO registration number: CRD42013005034